Complex bacterial diversity in the white biofilms of the Catacombs of St. Callixtus in Rome evidenced by different investigation strategies. (11th February 2015) - Krakova, Lucia; De Leo, Filomena; Bruno, Laura; Pangallo, Domenico; Urzì, Clara
Summary: Roman Catacombs are affected by different kinds of biofilms that were extensively investigated in the last 14 years. In particular, the areas far from the lamps are often covered by white biofilms of different extension, consistency and nature. The aim of this paper is to describe the profile of the microbial community present in two areas of the Ocean's Cubiculum (CSC13), characterized by similar alterations described as white biofilms, by using a multistep approach that included direct microscopy observations, culture‐dependent and culture‐independent methodologies through the extraction of DNA and RNA directly from the sampled areas. In addition to this, we extracted the DNA directly from the Petri dishes containing R2A and B4 media after incubation and growth of bacteria. Our results evidenced that a complex bacterial community (mainly constituted by filamentous Actinobacteria, as well as Firmicutes and Proteobacteria) colonizes the two different white biofilms, and its detection, quantitative and qualitative, could be revealed only by different approaches, each method giving different information that only partially overlap.